A 5-year-old boy with miliary and osteoarticular tuberculosis - Washington C.H. (BMJ Publishing Group, 2014)
Osteoarticular involvement is one manifestation of extrapulmonary tuberculosis (TB). We present a 5-year-old Burmese boy with 10 months of right hip pain and decreased range of motion. The patient also had low-grade fever, cough and decreased appetite. The patient was undocumented and had recently moved from Myanmar. He was thin, in moderate distress with bilateral lung rhonchi, mild subcostal retractions, low back pain, right hip tenderness and painful and limited right range of motion. The patient's chest and pelvis radiographs showed a miliary pattern and right acetabulum osteolytic lesions, respectively. He was started on anti-TB medication and cefotaxime. Ofloxacin was added because of the concern of drug-resistant TB. The patient underwent a right hip debridement. His symptoms improved markedly, with improved mobility. TB is a challenging infection to diagnose, which can cause significant delays in management. Copyright 2014 BMJ Publishing Group. All rights reserved.